2003
DOI: 10.1034/j.1399-0012.2003.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced P‐selectin expression on circulating platelets after prolonged cold preservation in renal transplantation

Abstract: The uremic state in patients with terminal renal insufficiency is accompanied by a bleeding tendency connected with platelet dysfunction. Prolonged cold ischemia and inflammatory interactions between leukocytes, platelets and endothelial cells contribute to ischemia-/reperfusion (I/R) injury and may impair long-term graft survival. We evaluated the influence of the duration of cold preservation time on the expression of platelet GPIIb/IIIa and P-selectin and on the formation of leukocyte-platelet complexes aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Whereas the EC 50 of the 100%, but not 21%, reoxygenated group was increased, the negative finding on the maximum aggregatory response (at 10 g/mL collagen) requires cautious interpretation. Nonetheless, this may indicate the reduced number of receptors and responsiveness of the platelets to collagen stimulation (19). Although it has been shown that exposure to hydrogen peroxide in vitro (20) or brief hyperoxia in vivo (21), even in the absence of hypoxia, inhibits both adenosine diphosphate (ADP)-and collagen-induced platelet aggregation, we speculate that the platelet aggregatory dysfunction is secondary to the hypoxia and reoxygenation injury.…”
Section: Discussionmentioning
confidence: 81%
“…Whereas the EC 50 of the 100%, but not 21%, reoxygenated group was increased, the negative finding on the maximum aggregatory response (at 10 g/mL collagen) requires cautious interpretation. Nonetheless, this may indicate the reduced number of receptors and responsiveness of the platelets to collagen stimulation (19). Although it has been shown that exposure to hydrogen peroxide in vitro (20) or brief hyperoxia in vivo (21), even in the absence of hypoxia, inhibits both adenosine diphosphate (ADP)-and collagen-induced platelet aggregation, we speculate that the platelet aggregatory dysfunction is secondary to the hypoxia and reoxygenation injury.…”
Section: Discussionmentioning
confidence: 81%
“…One study showed that rolling platelets along the endothelium occurred after I/R injury (Massberg et al, ). After stimulation, P‐selectin is transported to the platelet surface by fusion of the alpha‐granule membrane with the plasma membrane, which is responsible for the adhesion of activated platelets to endothelium (Scheinichen et al, ). Activated platelets contacting with endothelial cells could aggravate endothelial lesions, which lead to severely renal hypoxia at a microcirculatory level and even plays a central role in the development of subsequent thrombotic microangiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric samples were prepared as previously described (10). Briefly, leukocytes were identified according to their high‐CD45 expression.…”
Section: Methodsmentioning
confidence: 99%